How Renewable Energy Consumption and Natural Resource Abundance Impact Environmental Degradation? New Findings and Policy Implications From Quantile Approach - Altinoz, Buket; Dogan, Eyup (Taylor & Francis inc, 2021)
The EKC literature has ignored the importance of natural resources on environmental degradation. Thus, this paper aims to investigate the impact of renewable energy consumption and the abundance of natural resources on CO2 emissions for a panel of 82 countries by using quantile regressions. Empirical results show that renewable energy consumption reduces CO2 emissions and its effect increases in higher quantiles. The impact on carbon emissions of natural resource abundance is negative at lower quantiles but positive at medium and higher quantiles. Also, the validity of the EKC hypothesis is confirmed for all quantiles, and an increase in trade openness and urbanization increases environmental degradation in lower and middle quantile levels; however, these determinants have negative impacts on carbon emissions at higher quantiles. Policy implications related to this outcome are further discussed in the study.
Keywords: Renewable Energy; Natural Resources; Pollution; Panel Quantile Approach